Latins in Roman (Byzantine) Histories - Müller, Samuel Pablo, author.
1 online resource.
Keywords: Samuel P. Müller offers here the first book-length study of the image of Latins in Byzantine historiography of the long twelfth century, a crucial period that witnessed an unprecedented intensification of Byzantine-Western relations. He notably argues against popular assertions that the image of Latins is "negative" and reflective of steadily mounting tension. Instead, Müller shows that Byzantine historiography can hardly be taken as evidence that the conquest of 1204 was the inevitable outcome of previous interactions. The representation of Latins is complex, ambivalent, and reflective of fickle and multifaceted Byzantine-Western relations. The book also highlights the need to focus on Byzantine identities and crucial, introspective motivations to which the image of Latins is subordinated.